Implementation guidelines of the walk-through and questionnaire techniques in the usability testing of the scrum method - Muhammad, A. Khairuddin; Wan Kadir, Wan Mohd. Nasir (2006)
A wrongly chosen software development method often leads to the increased development cost or possible failure of a project. Therefore, a software development method should be systematically evaluated in order to measure its suitability for a particular type of project settings. Recently, there is an increasing interest in using usability test to evaluate the usability of software products and processes. In this paper, we will investigate the guidelines on using two usability testing techniques namely Walk-Through and Questionnaire, which are chosen due to the minimum involvement of human subjects. We describe the recommended ways of creating the usability test materials, analyzing the collected data, and creating a report based on the usability test results. The test is carried out to evaluate the use of Scrum method in the Tabung Baitulmal Sarawak (TBS) web-based system. The results presented in this paper are expected to provide software engineers with a systematic guideline in performing Walk-Through and Questionnaire as their usability testing techniques.